Traditional medicine in the treatment of gastrointestinal diseases in northern part of Kashmir Himalayas - Khoja, Aadil Abdullah; Andrabi, Syed Aasif Hussain; Mir, Rayees Afzal (Ethnobotany Research and Applications, 2022)
Background: Treatment of gastrointestinal diseases with medicinal plants from the northern portion of the Kashmir Himalayas is widespread, because of effectiveness, ease of availability, lack of modern healthcare alternatives, cultural preferences, and century-old affinity with the plants. Thus this vast supply of traditional knowledge must be documented as soon as feasible if sustainable healthcare systems are to be developed. Methods: This survey was conducted from June 2020 to September 2021 to document the indigenous knowledge on plant resources of the tribal communities of the administrative district Kupwara, Kashmir Himalayas. The data was gathered through open-ended semi-structured interviews and group discussions. Various statistical indices (UV & ICF) were used to further examine quantitative data. Results: A total of 67 plant species representing 31 families are reported to treat different gastrointestinal diseases, with herbs being the most dominant used plants (93%). Leaves (36%) are most frequently used in the study area followed by roots (33%) with preparation being dominated by infusion. Present study revealed that abdominal pain (23.88%) is the dominant disease which is treated using quoted medicinal herbs followed by constipation (17.91%), stomachache (16.42%). The reported ICF is very high I.e. (0.91- 0.96) indicating that the traditional knowledge about medicinal plants used to cure gastrointestinal diseases in district Kupwara is very extensive. Highest UV has been reported for Aconitum heterophyllum (0.96) and the lowest UV is recorded for Verbena officinales (0.17). Conclusion: The goal of this study was to highlight the potential for medicinal plants to be used to treat a variety of gastrointestinal ailments. Ten medicinal plants for the treatment of gastrointestinal issues were discovered for the first time in this part of Himalaya. The phytochemical content and pharmacological effects of these should be explored and there is a need for more research for conservation strategies. Keywords: Gastrointestinal, Traditional Knowledge, Ethnomedicine, Kupwara, Medicinal plants.